Community Empowerment in Making Natural Soap from Used Cooking Oil and Red Ginger - Haryanto, Sri; Lestari, Lilla Puji; Yahya, Sitti Rachmawati; Pandey, Digvijay; Indriyani, Indriyani (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Used cooking oil can be reused, one of which is to make liquid soap. Used cooking oil is first filtered and then clarified with activated carbon. This study aims to process used cooking oil into liquid soap by adding the red ginger extract to the formula. The method used in this research is the descriptive method. The results of this study showed that the liquid soap sample containing a red ginger extract did not meet the applicable standards based on several test parameters. Therefore, further research and development are needed to improve the composition of soap-making ingredients so that they can produce products that are more effective when used in everyday life.